Resting-state theta/beta EEG ratio is associated with reward- and punishment-related reversal learning - Schutte, Iris (Cogn Affect Behav Neurosci, 2017)
Prior research has shown that the ratio between resting-state theta (4–7 Hz)-beta (13–30 Hz) oscillations in the electroencephalogram (EEG) is associated with reward- and punishment-related feedback learning and risky decision making. However, it remains unclear whether the theta/beta EEG ratio is also an electrophysiological index for poorer behavioral adaptation when reward and punishment contingencies change over time. The aim of the present study was to investigate whether resting-state theta (4–7 Hz)-beta (13–30 Hz) EEG ratio correlated with reversal learning. A 4-min resting-state EEG was recorded and a gambling task with changing reward-punishment contingencies was administered in 128 healthy volunteers. Results showed an inverse relationship between theta/beta EEG ratio and reversal learning. Our findings replicate and extend previous findings by showing that higher midfrontal theta/beta EEG ratios are associated with poorer reversal learning and behavioral adaptive responses under changing environmental demands.